Penerapan Pentingnya Keselamatan Dan Kesehatan Kerja (K3) Pada Bengkel Las Umum Kelurahan Debong Kulon Kecamatan Tegal Selatan Kota Tegal - Akhmadi, Amin Nur; Usman, Mukhamad Khumaidi (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
Occupational safety and health are very important things in the work environment. They cover a wide range of measures and policies aimed at protecting employees from the risk of injury, illness, or other dangers that may arise in the context of their work. This involves identifying potential risks in the workplace, training for employees, and safe use of equipment. Occupational safety and health (K3) in the welding workshop plays a very crucial role because the welding process involves various potential risks and dangers that can have an impact on workers for several reasons. After all, it can prevent and reduce the risk of accidents and injuries, protect workers' health, and comply with regulations. And safety standards, increasing productivity and efficiency. To implement the tri dharma of higher education for DIII Mechanical Engineering lecturers, providing knowledge and skills regarding the application of the importance of occupational safety and health for employees of the General Welding Workshop. This service uses a direct practical presentation method in the workshop where the chairman gives directions to the welders to use work safety equipment directly; from this activity, it can be found that most welders always ignore work safety in terms of eye protection and hand and head protection. It was concluded that there was an increase in knowledge among residents of Debong Kulon Village, especially welding workshop employees, about the importance of Occupational Safety and Health / K3 for the safety and health of both humans and the environment.